2008
DOI: 10.1063/1.3044464
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved holographic optical coherence imaging using a high-sensitivity photorefractive polymer device

Abstract: We present coherence-gated holographic imaging using a highly sensitive photorefractive (PR) polymer composite as the recording medium. Due to the high sensitivity of the composite holographic recording at intensities as low as 5 mW/cm2 allowed for a frame exposure time of only 500ms. Motivated by regenerative medical applications, we demonstrate optical depth sectioning of a polymer foam for use as a cell culture matrix. An axial resolution of 18 μm and a transverse resolution of 30 μm up to a depth of 600 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The non‐cross‐linkable polymers can be applied as hole‐transporting materials in blended single‐layer devices, e.g., for photorefractive holographic application purposes. It has been shown that recording can be significantly faster using TPD derivatives instead of the common poly( N ‐vinylcarbazole) ( PVK ) 13. Here, we will focus on the application of the cross‐linkable polymers as HTLs in solution‐processed, multilayer OLEDs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The non‐cross‐linkable polymers can be applied as hole‐transporting materials in blended single‐layer devices, e.g., for photorefractive holographic application purposes. It has been shown that recording can be significantly faster using TPD derivatives instead of the common poly( N ‐vinylcarbazole) ( PVK ) 13. Here, we will focus on the application of the cross‐linkable polymers as HTLs in solution‐processed, multilayer OLEDs.…”
Section: Resultsmentioning
confidence: 99%
“…The polymers contain tetraarylbenzidines or tetraarylphenylenediamines as charge‐transporting units in the backbone connected by a non‐conjugating fluorene bridge. The non‐cross‐linkable materials are very promising for photorefractive application,13 whereas the cross‐linkable analogs due to their good film‐forming properties were demonstrated to be excellent candidates for improving charge injection in OLEDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-known example is the optical correlation of 2-dimensional data sets through the conditions under 830 nm cw-illumination, the PF6-TPD based material reveals a 250-fold faster response (considering time needed to reach 10% internal diffraction effi ciency) compared to the well-known PVK/TNFM composition. [ 69 ] The high sensitivity of this novel material allowed for depth-resolved imaging of a biodegradable polyurethane foam with 500 ms image acquisition time [ 226 ] and a rat osteogenic sarcoma tumor spheroid with a data acquisition speed of 8 × 10 5 voxels s − 1 and a dynamic range of 20 dB [ 69 ] (see Figure 22 ). Those numbers are comparable to holographic imaging operations performed from turbid and highly scattering media by coherence gating.…”
Section: Image Processing Operationsmentioning
confidence: 99%
“…7 Recently, photorefractive polymer composites were applied as the recording medium using a femtosecond pulsed Ti:sapphire laser with a wavelength ͑͒ near 840 nm. 8 Semiconductor CdTe crystals doped with vanadium and other 3d elements are very promising NIR photorefractive materials. 9 The photosensitivity range of CdTe crystals extends to about 1000 nm.…”
mentioning
confidence: 99%